Clinostomum Sinensis in Red-crowned Cranes (Grus japonensis) and in White-naped Cranes (Grus vipio) - Morphology and Molecular Characterization - Wang, Feiyan (2024)
Background: Clinostomum spp. are digenetic trematode parasites of freshwater snails and fishes, fish-eating birds, and humans. There are widely distributed around the world. The metacercariae of the Clinostomum can cause fish trematodes, and adults parasites parasitized in the throat and esophagus of fish-eating birds. The red-crowned crane (Grus japonensis) and white-naped cranes (Grus vipio) are internationally recognized as an endangered species. They are large wading bird species and listed as Class I protected animals in China. To date, there have been no reports of Clinostomum infection in red-crowned cranes (Grus japonensis) and white-naped cranes (Grus vipio) in China.  Materials, Methods & Results: In this study, we isolated specimens of Clinostomum sinensis adults from the oral cavity of red-crowned cranes (Grus japonensis) and white-naped cranes (Grus vipio) and encysted “yellow grub” metacercariae from the forage fish Pseudorasbora parva and used morphological analysis and molecular characterization based on 18S ribosomal RNA and the mitochondrial cytochrome oxidase (COI) loci. The digestive system of the metacercariae was clear, whereas the genital system was not, with the exception of the vitellaria. Morphological features of adults included a small oral sucker, an unclear or absent pharynx, a medium-sized ventral sucker, an ovoid cirrus pouch near the anterior testis, and a uterine sac that extended to the ventral sucker with no folds, especially the entire anterior testis offset to the left by the uterine sac and cirrus sac, and genital pore opening on the right side of the anterior testis and papillae around, compared with the features of other species of Clinostomum. At the 18S loci, the species was in the same clade with C. complanatum from Italy and Israel. It speculated that although the specimens sequenced in this study grouped with the sequences of C. complanatum from Asia, there are so few species that have been sequenced (and verified) that identification of the sequences in this study is still problematic. At the COI loci, Clinostomum spp. were clearcutted into different clades depending on geographical regions. The species isolated in this study was in the same clade as isolates from Asia. While, based on 18S or COI loci sequences analysis, the isolated specimens were identified as C. sinensis. Morphological observation also identified the precise species was C. sinensis. Above of all, we isolated C. sinensis from cranes and P. parva in eastern China firstly, and firstly descripted the morphology of adult of C. sinensis in eastern China.  Discussion: Precise species identification is crucial for controlling and treating parasite infections. Traditionally, morphological characteristics have been used to identify trematode species, although larval stages pose challenges due to fewer features. Molecular methods have proven effective, especially for morphologically similar species. This study identified C. sinensis in red-crowned (Grus japonensis) and white-naped cranes (Grus vipio) and their intermediate host P. parva in eastern China, using both morphology and molecular methods. Morphological analysis showed similarities with previous studies, with clear identification of the oral and ventral suckers in metacercariae, and specific features in adults such as the small oral sucker and ovoid cirrus pouch. Molecular analysis using 18S rRNA and COI loci revealed that the isolates clustered with C. complanatum and C. sinensis from Asia, with minimal sequence differences, confirming the specimens as C. sinensis.  Keywords: trematodes, Clinostomum sinensis, Clinostomum spp., crane, morphology, 18S rRNA, COI.